2016
DOI: 10.1093/omcr/omw049
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker malfunction associated with proton beam therapy: a report of two cases and review of literature—does field-to-generator distance matter?

Abstract: It is well known that radiotherapy causes malfunctions of cardiac implantable electronic devices such as pacemaker (PM) and implantable cardioverter-defibrillator because of incidental neutron production. Here, we report our experience with two cases of PM reset among seven patients with PM who underwent proton beam therapy (PBT) from January 2011 to April 2015 at our centre. Our experience shows PM reset can occur also with abdominal PBT. In both cases, PM reset was not detected by electrocardiogram (ECG) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…To our knowledge this is the first cohort reporting management of CIED patients undergoing carbon ion radiotherapy and one of the largest cohorts reported on patients with CIED undergoing proton radiotherapy. According to our experience the active scanning beam application mode can be applied with a high grade of safety compared to passive scattering where device malfunction rates of ~20 to 28.6% have been reported previously by others under similar treatment set-up conditions [with pulse generators outside the treatment fields in all cases and restriction to 2 Gy(RBE) and below by Gomez et al (10)] (1012).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…To our knowledge this is the first cohort reporting management of CIED patients undergoing carbon ion radiotherapy and one of the largest cohorts reported on patients with CIED undergoing proton radiotherapy. According to our experience the active scanning beam application mode can be applied with a high grade of safety compared to passive scattering where device malfunction rates of ~20 to 28.6% have been reported previously by others under similar treatment set-up conditions [with pulse generators outside the treatment fields in all cases and restriction to 2 Gy(RBE) and below by Gomez et al (10)] (1012).…”
Section: Discussionsupporting
confidence: 58%
“…Ueyama et al (12) reported two cases of resets to VVI backup mode in a series of seven patients treated by passive scattered protons. One patient received thoracic radiotherapy for bronchial cancer and one abdominal for pancreatic cancer and in both cases resets were not detected by ECG and were not clinically apparent otherwise (12).…”
Section: Discussionmentioning
confidence: 99%
“…Hazards linked to the effects of secondary neutrons on CIEDs may cause clinical problems in CIED-wearing patients. Current data about particle therapy with CIEDs carriers originate from in vitro experiments and clinical studies that are from single institutions and usually include a limited number of patients [9][10][11][12]. Recently, recommendations from AAPM have stated that particle beam therapy should be avoided for patients with CIED since it produces secondary neutrons [13].…”
Section: Introductionmentioning
confidence: 99%
“… 45 There was also a report that CIED reset can occur despite not being detected by electrocardiogram monitoring; instead, it was uncovered by posttreatment programmer analysis. 46 Modern CIEDs have CMOS which can tolerate doses of more than 2 Gy 47 , 48 ; however, the proton machine design has an effect on the CIED due to the overall physical environment around the patient. The pencil beam scanning system snout creates a relatively strong magnetic field around the patient, which may induce CIED malfunction.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%
“…17 Therefore, each patient needs to be considered individually and recognition of the patient's dependence on the CIED identified. If the patient is pacing-dependent, it is usually not recommended to treat them with proton therapy, 45 , 46 , 49 especially in standalone centers with limited resources. Likewise, for the pacing independent patient, risks should be evaluated before delivering proton therapy.…”
Section: Management Of Commonly Seen Implanted Devices In Rt Patientsmentioning
confidence: 99%